Análise de fácies e estratigrafia de sequências no Membro Funil, Paleoproterozoico do Escudo das Guianas - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The sedimentary evaluation and application of sequence stratigraphy concepts in Precambrian rocks are less frequent concerning Phanerozoic age, mainly linked to the high recycling rate of the Precambrian crust and to recrystallization processes that hinder the establishment of stacking patterns and stratigraphic surfaces. However, Precambrian sedimentary successions with broad exposures and well-preserved sedimentary structures of the Funil Member distributed in Serra do Tepequém (RR) represents an excellent opportunity to understand how sedimentation responds to high-frequency variations of the coastline and thus provide a better stratigraphic correlation of these exposures with the Roraima Supergroup. Because of these conditions, this research presents the facies analysis and stratigraphic sequence in the Funil Member with the objective of providing criteria of distinction between the units of the mountain, understanding the deposition of the unit in the context of eustatic variations and making considerations on Guiana Shield paleogeography. The facies analysis identified 13 facies that comprise tidal flat with paleoshoreline oriented to NE-SW, in the Paleoproterozoic context, that include deposits of braided river channels, tidal channels, mud and mixed flats. The Funil Member represents the distal portion related to the continental lake deposits of the Arai Formation of the Roraima Supergroup, in the extreme northeast of Roraima State. The unit is organized in 4th order deepening and thickening upward sequences limited by marine flooding surfaces, represented by the overlapping of mud flat deposits, mixed flat and thickening of tidal channel deposits, which configure a retrogradational stacking included in the transgressive systems tract of the lower sequence of the Roraima Supergroup. The 4th order sequences are internally marked by layers with an upward thinning pattern separated in fluvial and transitional domains. This stratum organization indicates the progressive creation of accommodation space linked to migration of the coastline to continent. The information generated here allowed, in an unprecedented way, the establishment of sequences in the Funil Member, in addition to a re-reading of the stratigraphy of the basal portion of the Roraima Supergroup in the light of concepts of the sequence stratigraphy.
Keywords: Cráton Amazônico; Geologia estratigráfica - Pré-cambriano; Thinning upward; Serra do Tepequém (Roraima); Paleogeografia; CIENCIAS EXATAS E DA TERRA; Cráton Amazonas; Pré-Cambriano; Formação Arai; Planície de maré